As engrenagens do capital no território do agreste central sergipano : o canto da sereia da odisséia do trabalho no novo eixo industrial calçadista - Barreto, Fábio de Jesus (2010)
The restructuring process presents itself as a mechanism of exit of capital for those moments of crisis. The process of capital accumulation that goes destructively search spaces where their reproduction may be made ever increasing scale, however, attempts to answers provided by capital in times of exacerbation of the crises that are given in the form of restructuring of the production process are no longer possible to be given, depending on the nature of the adversarial system, which shows that capitalism can only leave their previous crises piling deeper contradictions that tend, sooner or later, the blow with increasing force. The successive crises that arise as the production of its contradictory process of expansion, just accentuating the destructive elements that arise as a product of that movement "comes and goes," and the more the destructive logic of reproduction, the more it exacerbates the contradictions arising this process. What if this universe can keep up with perverse exploitation of labor is the reconfiguration of the working world in a way to extract the most value ever seen, even by resorting to violent mechanisms of extraction of surplus value, this exclusionary process and often violent exploitation of the work reflected on the working class in the form of child labor, slave labor, excessive working hours, low wages and exclusion of young and old production process. These elements present in the process of establishing the industrial structure can be clearly observed within the rough central Sergipe, where before the advance of industrial footwear axis has been accompanied by the salaried employees thereof, which has its living conditions debased by precarious employment relationships existing, which most often are shrouded by the "hand of the state", which works as an instrument of capital deleted all their labor rights historically achieved.